What is the financial cost of trade credit ? - Santos Jiménez, Néstor (2000)
Trade credit or financing provider biene and services is prevalent in e business world . basic carcateristica for the company that makes use of this type of financing is the ease of consultation , is part of the purchase with facilities . If the company CONASE own resources and / or alternative forms of financing for cmoprar cash, from a financial point of view, the credit provider is highly expensive. the implicit cost of trade credit to the purchasing company is because it desaprocecha the opportunity to use the discount is available for prontopago provider offers .biene to purchase capital financing provider should be medium and long term; is appropriate that the company will make with the supplier a sale price in cash, so that interest ( explicit cost ) is recognized by the debit balance , it is possible to use the " tax shield " of interest , since them the company buyer 's recorded as financial expenses.